Rethinking food aid to fight AIDS - Kadiyala, Suneetha; Gillespie, Stuart (International Food Policy Research Institute, 2003)
HIV/AIDS is a slow-moving, devastating shock that kills the most productive members of society, increases household dependency ratios, reduces household productivity and caring capacity, and impairs the intergenerational transfer of knowledge. It is socially invisible, complicated by silence, denial, stigma, and discrimination. While it affects both rich and poor, it is the poor who are most severely impacted. Though it affects both sexes, it is not gender neutral. Though AIDS is far more than just another health problem, many development organizations have yet to undertake thorough analyses of its impact on what they do and how they do it. Even fewer have actually changed their policies and procedures to adjust to the new realities. In the era of AIDS, food and nutrition security is becoming even more of a priority for many households and communities. We know that food and nutrition are fundamentally intertwined with HIV transmission and the impacts of AIDS. Evidence of the ways in which food insecurity and malnutrition may increase susceptibility to HIV as well as vulnerability to AIDS impacts, and how HIV/AIDS in turn exacerbates these conditions is increasingly well documented. Food and nutrition security is fundamentally relevant to all four of the conventional pillars of HIV/AIDS response -- prevention, care, treatment, and mitigation --and food aid can be an important addition to the arsenal. This paper, based on a detailed review of the relevant literature and the findings of a mission to eastern and southern Africa, highlights the implications of the HIV/AIDS pandemic for food aid strategy and programming. By viewing food aid programs through an HIV/AIDS lens" and in the context of a livelihoods approach, the authors argue that organizations can design effective interventions that reduce both susceptibility to HIV and vulnerability to AIDS impacts. Though there is little empirical evidence regarding the effectiveness of food aid in responding to HIV/AIDS, the authors argue this should not constrain action. Using past experience as a guide, organizations can learn by doing, documenting, and continuously reassessing their programs using the evolving HIV/AIDS lens. By doing so, they ensure maximal relevance and impact.." -- from Authors' Abstract